A Specific Routing Protocol for Flying Adhoc Network - Bashir Olaniyi Sadiq; Adewale Emmanuel Adedokun; Mohammad Bashir Mu’azu; Yusuf Abubakar Sha’aban (Universitas Ahmad Dahlan, 2018)
This paper presents a novel data and timed control routing protocol which is Flying Adhoc Network (FANET) specific. The developed FANET specific routing protocol laid emphasis on the route connectivity in the network by considering the captured data size, minimum allowable distance between randomly moving nodes and connection time. The performance of the proposed FANET specific routing protocol was simulated using NS3. The obtained throughput value for the routing protocol fluctuated between 742.064kbps and 755.083kbps as data are exchanged between nodes. This showed that when all the UAVs are on the network and communicating with one another, the throughput is flatline and not plummet. This implies consistency as nodes join and leave the network. The packet delivery ratio obtained for the FSRP during simulation was 96.13%. These results implied that data is successfully transmitted between the UAV acting as server and UAV acting as client on the network.